Restorative Management and Treatment of Pseudo-Class III Malocclusion - Ali H. Alfaifi (Case Reports in Dentistry)
Introduction. One of the challenges that clinicians encounter in the dental office is treating occlusal discrepancies. Malocclusion has been classified into three main classes that were further classified by researchers into more detailed subclasses later on. Pseudo-class III malocclusion has been called apparent or positional class III malocclusion, and its treatment usually consists of different modalities depending on how early the case is treated. When early orthodontic intervention was not possible, the restorative treatment becomes an excellent alternative especially when the teeth require restorative rehabilitation. Treatment. In this case report, the patient was suffering from dental wear, multiple failed old restorations, and edge-to-edge occlusal relationship which could be classified as pseudo-class III malocclusion. The patient’s esthetic complaint was addressed with full-coverage lithium disilicate and monolithic zirconia restorations that were successful in reestablishing the patient’s occlusal relationship and were able to eliminate the biological manifestations of dental caries. Conclusion. We were able to provide an alternative to orthodontic treatment where esthetic and functional needs of the patient were met after careful diagnosis and proper management. This clinical approach will give chance to treat patients suffering from minor occlusal discrepancies that require restorative intervention without the need to go through orthodontic therapy.